Process and Controlling Factors of Pore Evolution in Marine-Continental Transitional Black Shale—An Example From Permian Shanxi Formation in the Eastern Margin of Ordos Basin - Wu, Jin; Zhang, Xiaowei; Xu, Hao; Xiao, Yufeng; Liu, Guiying; Jiang, Lingfeng; Deng, Naier; Ren, Zihe (Frontiers in Earth Science, 2022)
Pore and pore network evolution of shale is critical for the evaluation the pore system in shale gas reservoirs. Thermal maturation effect acts as an indispensable role in porosity evolution. In this paper, high-temperature and high-pressure in-situ thermal simulation experiments were conducted to investigate the process and controlling factors of pore evolution in marine-continental transitional shale. Multiple methods, including scanning electron microscopy (SEM), X-ray diffraction, helium porosimetry and low-pressure N2 and CO2 adsorption were used to investigate the evolution of mineral composition and pore structure at different stages of thermal maturity. The results showed that type III organic matter (OM) generated petroleum with the thermal maturity increasing. The total organic carbon (TOC) decreased by 13.3% when temperature reached 607°C. At the same time, it produced numerous organic and mineral pores during hydrocarbon generation. Besides, some changes in mineral composition have occurred, especially in illite (from 11% to 31%) and kaolinite (from 89% to 69%). In general, it can divide into 3 stages (maturity, high maturity and over maturity) for shale pore system evolution with the thermal maturity increasing. In the low maturity period, large amounts of pyrolytic bitumen and oil generated to fill the pores, causing the pore system to diminish; in the high maturity period, a large number of pores were generated when oil is cracked into gas, resulting in a rapid expansion of the pore system; in the over-maturity period, the cracking of pyrolysis and hydrocarbon slowed down, allowing the pore system to stabilize. Shale pore evolution is primarily controlled by the thermal evolution of OM, and the conversion of inorganic minerals contributes less to pore evolution compared to organic matter. The high maturity period (1.2% < Ro < 2.0%) was the period when extensive pyrolysis and hydrocarbon generated in the Shanxi Formation shale, which contributed mostly for the pores generation and accumulation of shale gas.